Spaces for the future : a companion to the philosophy of technology - Pitt, Joseph C. (New York : Routledge, 2017)
"Focused on mapping out contemporary and future domains in philosophy of technology, this volume serves as an excellent, forward-looking resource in the field and in cognate areas of study.? The 32 chapters, all of them appearing in print here for the first time, were written by both established scholars and fresh voices.? They cover topics ranging from data discrimination and engineering design, to art and technology, space junk, and beyond.? Spaces for the Future: A Companion to Philosophy of Technology is structured in six parts: (1) Ethical Space and Experience; (2) Political Space and Agency; (3) Virtual Space and Property; (4) Personal Space and Design; (5) Inner Space and Environment; and (6) Outer Space and Imagination. The organization maps out current and emerging spaces of activity in the field and anticipates the big issues that we soon will face. "--Provided by publisher.
part 1 Ethical Space and Experience -- chapter 1 Data, Technology, and Gender -- Thinking About (and From) Trans Lives / Anna Lauren Hoffmann -- chapter 2 Discrimination / D. E. Wittkower -- chapter 3 Video Games and Ethics / Monique Wonderly -- chapter 4 Social Networking -- The Dialectics of Sharing / Yoni Van Den Eede -- chapter 5 Technoart / Don Ihde -- chapter 6 The Philosophy of Art and Technology / Jessie Mann -- part 2 Political Space and Agency -- chapter 7 Robots With Guns / Shannon Vallor -- chapter 8 Educational Technology / Andrew Wells Garnar -- chapter 9 Religious Transcendence / Carl Mitcham -- chapter 10 Agency and Citizenship in a Technological Society / Andrew Feenberg -- chapter 11 Animals in Philosophy of Technology / Ashley Shew -- part 3 Virtual Space and Property -- chapter 12 Obscurity and Privacy / Evan Selinger -- chapter 13 Copyright Between Economic and Cultural Models of Creativity / Gordon Hull -- chapter 14 Cyberwarfare / Benjamin C. Jantzen -- chapter 15 The Cloud / Craig A. Condella -- chapter 16 Ethical Issues in Big Data / Deborah G. Johnson -- chapter 17 Virtual Environments / Johnny Hartz Søraker -- part 4 Personal Space and Design -- chapter 18 The Organization of User Experience / Robert Rosenberger -- chapter 19 Engineering Design / Pieter E. Vermaas -- chapter 20 Design / Ann Johnson -- chapter 21 Dancing the Device -- A Translational Approach to Technology / Albrecht Fritzsche -- chapter 22 On Harnessing of Birth in the Technical Age / Dana S. Belu -- chapter 23 Moore s Regula / Cyrus C. M. Mody -- part 5 Inner Space and Environment -- chapter 24 Is Renewable Energy Technology Revolutionary? / Robert Darrow -- chapter 25 Geoengineering and Climate Change / Tina Sikka -- chapter 26 Fracking / Adam Briggle -- chapter 27 Climate Change and Philosophy of Technology / Robert-Jan Geerts -- part 6 Outer Space and Imagination -- chapter 28 Space Tourism and Science Fiction / Rosalyn W. Berne -- chapter 29 Well-Ordered Engineering -- Participatory Technology Assessment at NASA / Zachary Pirtle -- chapter 30 When Loving Your Planet Isn t Enough / Diana P. Hoyt -- chapter 31 Transcendence in Space / Joseph C. Pitt -- chapter 32 The Role of Technology in Natural Science / Nicholas Rescher.
Keywords: Technology -- Philosophy